Photo-thermal driven regenerated carbon dioxide trapping material as well as preparation method and application thereof

By adding manganese trioxide and co-impregnation modifier to the silicon-based solid amine adsorbent, the spectral absorption rate and adsorption capacity are improved, the problem of low regeneration efficiency of traditional adsorbents is solved, and efficient carbon dioxide capture and regeneration driven by photothermal is achieved.

CN119909644APending Publication Date: 2025-05-02NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510249176.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing silicon-based solid amine carbon dioxide adsorbent has low spectral absorption rate, resulting in low regeneration efficiency and high energy consumption of traditional thermal regeneration methods.

Method used

The photothermal-driven regenerated carbon dioxide capture material is used to increase the adsorption capacity and regeneration efficiency by adding manganese trioxide to the silicon-based carrier as a spectral absorption enhancer, and using polyethylene glycol 200 to co-imide with polyethyleneimine.

Benefits of technology

It significantly improves the spectral absorption rate and adsorption capacity, achieves efficient regeneration under light and heat, and reduces energy consumption and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119909644A_ABST
    Figure CN119909644A_ABST
Patent Text Reader

Abstract

The invention discloses a photo-thermal driven regenerated carbon dioxide trapping material as well as a preparation method and application thereof. The trapping material comprises a silicon-based carrier, a binder, a spectral absorptivity enhancer, a heat-conducting additive, polyvinyl alcohol, an amido-containing impregnation modifier and a co-impregnation additive, the mass ratio of the silicon-based carrier to the binder to the spectral absorptivity enhancer to the heat-conducting additive is 100: (20-50): (4-6): (1-10). The preparation method comprises the following steps: adding manganese sesquioxide into silica gel, a binder and a heat-conducting additive to serve as a spectral absorptivity enhancer, and performing extrusion, rolling and calcination to obtain carrier particles; amine and polyethylene glycol are dissolved together in a solvent, and the carrier particles are modified by co-impregnation. The spectral absorptivity of the prepared carbon dioxide trapping particles is improved by 61%, the adsorption performance of the particles is further improved under 4.5 kW / m < 2 > illumination, the temperature can be increased to 74 DEG C within 30 min, and regeneration is basically completed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon dioxide capture, and specifically relates to a photothermal driven regeneration carbon dioxide capture material and a preparation method and application thereof. Background Art

[0002] With the development of global industrialization and urbanization, the consumption of primary energy has increased dramatically, resulting in a rapid growth trend in the emission of carbon dioxide in the atmosphere, which has led to problems such as climate change and global warming. If the current rate of carbon emissions continues, humans and even the global ecosystem will face a huge survival crisis. Therefore, in recent years, the world has paid more attention to atmospheric carbon dioxide emissions and has made a series of efforts, including reducing the use of fossil energy, developing efficient energy utilization devices, increasing the use of renewable energy, reducing carbon dioxide emissions in the atmosphere, etc. Among them, carbon capture technology can effectively reduce carbon emissions and promote global carbon neutrality, thereby alleviating these environmental challenges.

[0003] Solid amine adsorbent technology has been widely studied as a promising carbon capture technology. Granulation technology for solid amine adsorbents can effectively alleviate the difficulties in its large-scale application process. In addition, due to the large thermal inertia of the adsorbent fixed bed system and the relatively small heat capacity of the gas used to heat the bed, traditional thermal regeneration often uses high desorption temperature and long heating time, which consumes a lot of energy. By using renewable energy such as light to drive desorption, the energy consumption and cost of regenerating the adsorbent can be potentially reduced. At present, most carbon dioxide capture materials are liquids and powders, and there is less research on particles. The regeneration cost of carbon capture accounts for a large part, and reducing energy consumption can help reduce regeneration costs. Summary of the invention

[0004] Purpose of the invention: In view of the problems existing in the prior art, the present invention provides a photothermal-driven regenerated carbon dioxide capture material. The photothermal-driven regenerated carbon dioxide capture material prepared by the present invention has excellent spectral absorption rate, adsorption capacity and adsorption-desorption rate, realizes efficient regeneration under photothermal conditions, and has a low cost, effectively solving the problems of low spectral absorption rate and low regeneration efficiency of existing traditional silicon-based solid amine carbon dioxide adsorbents.

[0005] The present invention also provides a preparation method and application of the photothermal driven regeneration carbon dioxide capture material.

[0006] Technical solution: In order to achieve the above-mentioned purpose, the present invention provides a photothermal driven regeneration carbon dioxide capture material, which includes a silicon-based carrier, a binder, a spectral absorption enhancer, a thermal conductivity additive, an amine-containing impregnation modifier and a co-impregnation additive, and the mass ratio of each substance is 100:20-50:4-6:1-10.

[0007] The silicon-based carrier is silica gel, and the amine-containing impregnation modifier and co-impregnation additive are polyethyleneimine (PEI) and polyethylene glycol 200 (PEG200) respectively.

[0008] Wherein, the binder is attapulgite and methyl cellulose, and the mass ratio of the two is 2-5:3.

[0009] Wherein, the spectral absorption rate enhancer is manganese trioxide, and the thermal conductive additive is BN.

[0010] The method for preparing the photothermal driven regeneration carbon dioxide capture material of the present invention comprises the following steps:

[0011] (1) mixing the silicon-based carrier, the binder, the spectral absorption enhancer, and the thermal conductive additive by ball milling;

[0012] (2) mixing the powder with the polyvinyl alcohol solution and kneading it into a dough, extruding it into granules, and calcining it into a shape;

[0013] (3) dissolving the amine-containing impregnation modifier and the co-impregnation additive in an organic solvent to form a solution, adding the calcined carrier particles to the solution, and removing the solvent to obtain a carbon dioxide capture material for photothermal driven regeneration.

[0014] Wherein, the concentration of the polyvinyl alcohol solution in step (2) is 2% to 5%, and the diameter of the extrudate after extrusion is 1-2 mm. The polyvinyl alcohol powder is dissolved in deionized water to form a solution, and granulated together with the powder.

[0015] Wherein, the calcination temperature in step (2) is 500-600°C and the calcination time is 10-15h.

[0016] Preferably, the calcination temperature in step (2) is 550° C. and the calcination time is 12 h.

[0017] Wherein, the organic solvent in step (3) is anhydrous methanol or anhydrous ethanol.

[0018] Wherein, the dosage ratio of the carrier particles to the solution in step (3) is 500 mg:10-20 ml.

[0019] Preferably, the method for preparing the photothermal driven regeneration carbon dioxide capture material comprises the following steps:

[0020] (1) Evenly mixing powders: mixing silica gel, attapulgite, methyl cellulose, boron nitride and manganese trioxide powders evenly by ball milling;

[0021] (2) Extrusion granulation: The powder is mixed with the polyvinyl alcohol solution and kneaded into a dough, and then granulated by extrusion spheronization;

[0022] (3) Calcination and molding: The particles are placed in a muffle furnace and calcined until they are formed;

[0023] (4) Modification by impregnation method: The amine-containing impregnation modifier polyethyleneimine (Mw ~ 800) and the co-impregnation additive polyethylene glycol 2000 are dissolved in a solvent to form a solution, and the calcined particles are added to the solution. After removing the solvent, the carbon dioxide capture particles for photothermal driven regeneration are obtained.

[0024] Furthermore, in step (1), the mass ratio of silica gel, attapulgite, methyl cellulose, boron nitride and manganese trioxide is 100:20:15:5:5, the ball milling speed is 600 rpm, and the ball milling time is 2-4 h.

[0025] Furthermore, in step (2), the concentration of the polyvinyl alcohol solution is 2% to 5%, and the diameter of the extrudate is 1 mm.

[0026] Furthermore, in step (3), the heating rate during calcination is 10°C / min, the calcination temperature is 550°C, the calcination time is 12h, and the room temperature is 20-35°C.

[0027] Furthermore, the solvent in step (4) is anhydrous methanol or anhydrous ethanol, the amine-containing impregnation modifier is branched polyethyleneimine (Mw~800), the polyethylene glycol uses polyethylene glycol 200, and the ratio of carrier particles to solvent is 500mg:10~20ml.

[0028] Preferably, the mass ratio of the carrier particles, polyethyleneimine (PEI) and polyethylene glycol 200 (PEG200) is 7:3:0.3-1.

[0029] Furthermore, the mass ratio of the carrier particles, polyethyleneimine (PEI) and polyethylene glycol 200 (PEG200) is 7:3:0.6.

[0030] The photothermal-driven regenerated carbon dioxide capture material of the present invention is used in carbon dioxide capture and adsorption.

[0031] The present invention adds manganese trioxide as a spectral absorption enhancer to silica gel, a binder, and a thermal conductive additive, adds a polyvinyl alcohol solution after uniform mixing, and preliminarily prepares particles by extrusion and spheronization; calcines the particles to obtain final carrier particles; dissolves amine and polyethylene glycol together in a solvent, and modifies the carrier particles by co-impregnation. The carbon dioxide capture particles prepared by the present invention are doped with manganese trioxide, and the spectral absorption rate is increased by 61%, and the absorption rate at 4.5kW / m 2Under light, the temperature can be raised to 74°C within 30 minutes, and regeneration is basically completed. At the same time, the adsorption performance of the particles is further improved by co-impregnation of polyethylene glycol 200 and polyethyleneimine.

[0032] The present invention aims to solve the problem of poor spectral absorption rate of silicon-based solid amine adsorbents by adding a specific proportion of manganese to improve the spectral absorption rate and achieve a good photothermal regeneration effect. Secondly, polyethylene glycol and polyethyleneimine are co-impregnated to further improve the adsorption capacity. Furthermore, in the preparation of the present invention, manganese is added by extrusion and spheronization to prepare a carbon capture adsorbent to improve the spectral absorption rate.

[0033] The present invention improves the spectral absorption rate of particles through specific raw material composition and proportion, achieving good desorption efficiency and photothermal regeneration effect.

[0034] In the present invention, manganese is added to the carbon dioxide capture adsorption material in a specific proportion for the first time. The addition of manganese in a specific proportion not only significantly affects the spectral absorptivity, but also can quickly achieve material regeneration. The amount of manganese added in the present invention is very important. Compared with particles without or with a small amount of manganese, the spectral absorptivity is significantly improved in the present invention, which helps to achieve rapid temperature rise desorption and material regeneration under light. In addition, when an excess of manganese is added, although the spectral absorptivity will also be improved to a certain extent, it will cause serious attenuation of the adsorption capacity. The specific manganese addition amount of the present invention achieves a significant increase in both spectral absorptivity and adsorption capacity, and a slight change in the amount of manganese added will lead to a significant reduction in the effect. In addition, the addition ratio of polyethyleneimine and PEG200 in the present invention is also very important. Compared with the carrier particles, the excessive or low content of polyethyleneimine and PEG200 will significantly affect the adsorption capacity of the material. The carbon capture material for photothermal driven regeneration proposed by the present invention based on silicon-based solid amine adsorbent particles is significantly improved compared to other liquid and powder forms.

[0035] The present invention is the first to improve the thermal conductivity of solid amine adsorbent particles by adding BN, wherein BN is thermally stable and hardly reacts at a high temperature of 500°C. By adjusting the amount of the thermal conductive additive added and granulating by extrusion and spheronization, the thermal conductivity and average desorption rate of the material can be significantly improved.

[0036] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0037] (1) The present invention introduces a specific manganese element into a porous carrier, and obtains the best carbon dioxide capture particles for photothermal driven regeneration through modification, and the photothermal regeneration performance is significantly enhanced.

[0038] (2) The material prepared by the present invention is prepared by co-impregnation of polyethylene glycol 200 and polyethyleneimine in a specific ratio to prepare carbon dioxide capture particles with better adsorption capacity.

[0039] (3) The carbon dioxide capture particles prepared by the present invention are simple to prepare and can be used for large-scale carbon dioxide capture or direct air capture. This is because traditional adsorbents are generally powders, which are prone to clogging when used on a large scale and have high energy consumption due to high pressure drop. The particles prepared by the present invention can effectively solve the above problems and are more suitable for various industrial adsorption devices such as fixed beds and fluidized beds, which is conducive to large-scale carbon capture, especially direct air capture. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a schematic diagram of the fixed bed CO2 capture and photothermal driven regeneration device used in the present invention;

[0041] Figure 2 is Spectral absorptivity of the carrier particles of the present invention;

[0042] Figure 3 This is the adsorption capacity diagram of the carbon dioxide capture particles of the present invention under room temperature conditions, carrier particles: PEI = 70:30;

[0043] Figure 4 This is the adsorption capacity diagram of the carbon dioxide capture particles of the present invention under room temperature conditions, carrier particles: PEI = 70:20;

[0044] Figure 5 is the photothermal temperature rise curve of the carbon dioxide capture particle of the present invention;

[0045] Figure 6 It is the simulated air CO2 adsorption curve and photothermal regeneration curve of the carbon dioxide capture particles of the present invention under a fixed bed. DETAILED DESCRIPTION

[0046] The present invention is further described below in conjunction with embodiments and drawings.

[0047] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources. Experimental methods without specific conditions specified in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0048] The raw materials and manufacturer's product numbers used in the present invention are shown in Table 1.

[0049] Table 1 Chemical reagents used and their detailed information

[0050]

[0051]

[0052] Example 1

[0053] Preparation of CO2 capture particles for photothermal driven regeneration

[0054] The main component of the carrier of the carbon dioxide capture particles is silica gel, and attapulgite, methyl cellulose, boron nitride, and manganese trioxide are added to granulate by extrusion spheronization. The carbon dioxide capture particles are finally prepared by co-impregnation with polyethyleneimine and PEG200. In this embodiment, the mass ratio of the carrier, PEI, and PEG200 is 7:3:0. The specific operation steps are as follows:

[0055] (1) Calculate the mass of silica gel, attapulgite, methyl cellulose, boron nitride (BN), and manganese trioxide. Weigh 10 g of silica gel, 2 g of attapulgite, 1.5 g of methyl cellulose, 0.5 g of BN, and 0.5 g of manganese trioxide. Add the powders together into a ball mill and grind them at 600 rpm for 2 h to obtain a uniformly mixed powder.

[0056] (2) 10 g of the ball-milled powder was mixed with 10 ml of a 5% by mass polyvinyl alcohol deionized water solution to form a paste, and the mixture was kneaded until the dough was not broken. The mixture was put into an extruder to produce a rod-shaped sample with a diameter of 1 mm. The rod-shaped sample was put into a spheronizer to spheronize the sample to form particles with a diameter of 1 mm.

[0057] (3) The particles were placed in a muffle furnace, heated to 550° C. at a heating rate of 10° C. / min, and calcined for 12 h to plasticize the particles, and then naturally cooled to room temperature to obtain carrier particles.

[0058] (4) 3 g of polyethyleneimine (Mw800) was dissolved in 20 mL of ethanol and stirred at room temperature for 1 h to fully dissolve PEI. The solution was transferred to a flask of a rotary evaporator, 7 g of carrier particles were added, and rotary evaporated at 50 ° C for 2 h. Then, it was placed in a vacuum drying oven and dried at 70 ° C overnight to obtain carbon dioxide capture particles for photothermal driven regeneration.

[0059] Example 2

[0060] The method of Example 1 is adopted. The difference between this example and Example 1 is that the mass ratio of the carrier, PEI and PEG200 is 7:3:0.6.

[0061] Example 3

[0062] The method of Example 1 is adopted. The difference between this example and Example 1 is that the mass ratio of the carrier, PEI and PEG200 is 7:3:1.

[0063] Example 4

[0064] The method of Example 1 is adopted. The difference between this example and Example 1 is that the mass ratio of the carrier, PEI and PEG200 is 7:3:2.

[0065] Example 5

[0066] The method of Example 1 is adopted. The difference between this example and Example 1 is that the mass ratio of the carrier, PEI and PEG200 is 7:3:3.

[0067] Example 6

[0068] The method of Example 1 is adopted. The difference between this example and Example 1 is that the mass ratio of the carrier, PEI and PEG200 is 7:2:0.

[0069] Example 7

[0070] The method of Example 1 is adopted. The difference between this example and Example 1 is that the mass ratio of the carrier, PEI and PEG200 is 7:2:0.6.

[0071] Example 8

[0072] The method of Example 1 is adopted. The difference between this example and Example 1 is that the mass ratio of the carrier, PEI and PEG200 is 7:2:1.

[0073] Example 9

[0074] The method of Example 1 is adopted. The difference between this example and Example 1 is that the mass ratio of the carrier, PEI and PEG200 is 7:2:2.

[0075] Example 10

[0076] The method of Example 1 is adopted. The difference between this example and Example 1 is that the mass ratio of the carrier, PEI and PEG200 is 7:2:3.

[0077] Comparative Example 1

[0078] The difference between this comparative example and Example 2 is that manganese trioxide is not added during the preparation of the carrier particles.

[0079] Comparative Example 2

[0080] The difference between this comparative example and Example 2 is that the amount of manganese trioxide added during the preparation of the carrier particles is 0.3 g.

[0081] The difference between this comparative example and Example 2 is that the amount of manganese trioxide added during the preparation of the carrier particles is 0.7 g.

[0082] Embodiment 11

[0083] The CO2 capture performance test uses a synchronous thermal analyzer to measure the adsorption capacity of the sample. The test process is divided into three stages:

[0084] (1) Pretreatment stage: Peel the crucible, weigh 8 mg of the sample prepared in the above example and put it into the crucible, introduce 100 ml / min of N2, heat from room temperature to 100°C at a heating rate of 10°C / min, and keep it at 100°C for 30 min to fully remove water, CO2 and other volatile gases in the adsorbent.

[0085] (2) Adsorption stage: Cool the furnace to the adsorption temperature of 35°C, switch to 15% CO2 (the rest is nitrogen), and perform adsorption for 1 hour to obtain the adsorption curve of the sample mass over time. If the adsorption process is measured under air conditions, switch to air and maintain for 4 hours.

[0086] (3) Desorption stage: The atmosphere was switched back to pure N2, and the temperature was raised from the adsorption temperature to 100°C at a heating rate of 10°C / min, and kept at 100°C for 30 min to complete the desorption process.

[0087] from Figure 3 It can be seen that when the carrier particle: PEI = 7:3, the use of a small amount of PEG200 for co-impregnation can significantly improve the adsorption capacity, while when more PEG200 is co-impregnated, the adsorption capacity is significantly reduced. Among them, the best adsorption performance is Example 2, which proves that it is very important to use a specific proportion of PEG200 during co-impregnation in the present invention.

[0088] from Figure 4 It can be seen that when the carrier particles: PEI = 7:2, PEG200 is used for co-impregnation. Regardless of the content of PEG200, the adsorption capacity after improvement is obviously not as good as that of Example 2 of the present invention.

[0089] Example 12

[0090] Photothermal driven regeneration test under fixed bed

[0091] The air-source carbon dioxide capture test system under a fixed bed consists of a gas cylinder, a mass flow meter, a xenon lamp light source, a fixed bed reactor and a gas analysis mass spectrometer. The gas distribution system consists of an air cylinder, an argon cylinder and a flow controller, which is used to switch gases in different test steps. Argon is used for purging in the desorption stage, and air is introduced in the adsorption stage. The CO2 concentration in the simulated air is about 430ppm, N2 is 79%, and the rest is O2. Argon is used as the purge regeneration gas. The fixed bed reactor is a customized quartz tube with a rectangular parallelepiped in the middle. The internal length, width and height are 20mm, 20mm and 2mm. The height is low enough to ensure that the light can fully heat the sample, and the two ends are supported by quartz wool. Figure 1This is a schematic diagram of a fixed-bed CO2 capture and photothermal-driven regeneration device. The carbon dioxide capture particles are placed in a rectangular space about 2 mm high and irradiated by a xenon lamp to achieve photothermal variable temperature regeneration.

[0092] The specific test steps are as follows:

[0093] (1) 400 mg of adsorbent particles prepared in different embodiments and comparative examples were loaded into a fixed bed reactor. First, 150 ml / min of argon was introduced into the reactor, and the temperature was raised from room temperature to 100°C and kept at 100°C for 30 min for pre-desorption. After the pre-desorption was completed, the temperature was lowered to room temperature, and the gas was switched to 200 ml / min simulated air for air source CO2 capture experiment, and the adsorption time lasted for 4 hours.

[0094] (2) After the adsorption is completed, switch to 150 ml / min of argon gas again to purge the pipeline gas for about 30 minutes, and then place the reactor under a xenon lamp light source for photothermal variable temperature desorption with an intensity of 4.5 kW / m2 for 2 hours. The power is 1.8 W.

[0095] (3) The gas at the reactor outlet is introduced into a gas analysis mass spectrometer for gas type and content analysis, and quantification is performed based on the size of the peak area in the mass spectrum detection graph.

[0096] Embodiment 13

[0097] The spectral absorption characteristics of the sample are detected using a UV-Vis-NIR spectrophotometer. The sample is placed in a sample cell for measurement, and the spectral absorbance is calculated using the formula within the wavelength range of 300-2000nm.

[0098] According to the method of Example 13, from Figure 2 It can be seen from the spectral absorption rate curve that the carrier particles used in Example 2 show better spectral absorption performance and significantly improved spectral absorption rate compared with Comparative Example 1 due to the addition of a small amount of manganese trioxide as a spectral absorption rate enhancer. Although Comparative Example 2 also adds manganese trioxide, its spectral absorption rate effect can only reach about 60%, which is almost the same as without addition. In Comparative Example 3, the amount of manganese trioxide added is increased. Although it can also improve the spectral absorption rate of the carrier particles, the capture particle material finally prepared will lead to a significant decrease in the particle adsorption capacity, which can only reach about 0.75mmol (CO2 / g), and its effect is obviously not as good as that of Example 2 of the present invention.

[0099] The determination was carried out according to the method of Example 12. Figure 5 It can be seen from the light heating curve that the prepared Example 2 has a high temperature at 4.5 kW / m 2The temperature rose to 74°C within 30 minutes under the same lighting conditions, which was significantly better than that of the comparative example 1 without adding manganese trioxide. This further illustrates that the particles of the present invention with a specific amount of manganese trioxide heated up faster and at a higher temperature under the same lighting conditions, which is more conducive to rapid desorption and regeneration. Figure 6 It can be seen that both Example 2 and Comparative Example 1 can reach saturation adsorption within 4 hours, and the photothermal driven desorption curve of Example 2 is sharper, and almost completely regenerated within 30 minutes. In comparison, the desorption peak of Comparative Example 1 is relatively gentle, and thermal desorption is required for complete regeneration. However, due to the low spectral absorption rate, Comparative Example 2 cannot be completely and quickly regenerated by light alone under the same conditions.

[0100] In summary, the material prepared by the present invention has a better adsorption capacity, and has a more significant regeneration effect and a faster regeneration rate in the photothermal carbon dioxide capture process.

Claims

1. A photothermal driven regeneration carbon dioxide capture material, characterized in that: The capture material comprises a silicon-based carrier, a binder, a spectral absorption enhancer, a thermal conductivity additive, an amine-containing impregnation modifier and a co-impregnation additive, wherein the mass ratio of the silicon-based carrier, the binder, the spectral absorption enhancer and the thermal conductivity additive is 100:20-50:4-6:1-10.

2. The photothermal driven regeneration carbon dioxide capture material according to claim 1, characterized in that: The silicon-based carrier is silica gel, and the amine-containing impregnation modifier and co-impregnation additive are preferably polyethyleneimine (PEI) and polyethylene glycol 200 (PEG200), respectively.

3. The photothermal driven regeneration carbon dioxide capture material according to claim 1, characterized in that: The binder is attapulgite and methyl cellulose, and the mass ratio of the two is 2-5:

3.

4. The photothermal driven regeneration carbon dioxide capture material according to claim 1, characterized in that: The spectral absorption rate enhancer is manganese trioxide, and the thermal conductive additive is BN.

5. A method for preparing the photothermal driven regeneration carbon dioxide capture material according to claim 1, characterized in that: The steps include: (1) mixing the silicon-based carrier, the binder, the spectral absorption enhancer, and the thermal conductive additive by ball milling; (2) mixing the powder with the polyvinyl alcohol solution and kneading it into a dough, extruding it into granules, and calcining it into a shape; (3) dissolving the amine-containing impregnation modifier and the co-impregnation additive in an organic solvent to form a solution, adding the calcined carrier particles to the solution, and removing the solvent to obtain a carbon dioxide capture material for photothermal driven regeneration.

6. The preparation method according to claim 5, characterized in that: In step (2), the mass ratio of the powder to the polyvinyl alcohol in step (2) is 1:1-2, the concentration of the polyvinyl alcohol solution is 2% to 5%, and the diameter of the extrudate after extrusion is 1-2 mm.

7. The preparation method according to claim 5, characterized in that: The calcination temperature in step (2) is 500-600° C. and the calcination time is 10-15 hours.

8. The preparation method according to claim 5, characterized in that: The organic solvent in step (3) is anhydrous methanol or anhydrous ethanol.

9. The preparation method according to claim 5, characterized in that: The dosage ratio of the carrier particles to the solution in step (3) is 500 mg:10-20 ml.

10. Use of the photothermal driven regenerated carbon dioxide capture material according to claim 1 in carbon dioxide capture and adsorption.

Citation Information

Cited By

  • Electrochemical regeneration and conversion method and system for carbon dioxide supported absorbent

    CN121490530A